Design of Control Strategy and Effect Evaluation for Primary Frequency Regulation of Wind Storage System - Li, Cuiping; Zhang, Zheshen; Li, Junhui; Ma, Yunbao; Zou, Jiajun (Frontiers in Energy Research, 2021)
Because of wind sources’ volatility and intermittent news, wind power has made a more and more heavy burden on the power system. To evaluate the effectiveness and economics of the primary frequency modulation of the power system, this paper considers the integrated control strategy considered both the parallel control strategy and serial control strategy, which is adopted by the energy storage system (ESS) and proposes an optimal control strategy of ESS. A comprehensive performance evaluation method for the primary frequency regulation of the ESS participating in the power grid is proposed based on the power system operation requirements. In the example, the frequency modulation performance of the optimal control strategy is verified by the evaluation method described in this paper in the Chinese frequency adjustment market.